The management and outcomes of placenta accreta, increta, and percreta in the UK: a population‐based descriptive study. (7th August 2013) - Fitzpatrick, KE; Sellers, S; Spark, P; Kurinczuk, JJ; Brocklehurst, P; Knight, M
<x xml:space="preserve">Abstract</x> Objective To describe the management and outcomes of placenta accreta, increta, and percreta in the UK. Design A population‐based descriptive study using the UK Obstetric Surveillance System (UKOSS). Setting All 221 UK hospitals with obstetrician‐led maternity units. Population All women diagnosed with placenta accreta, increta, and percreta in the UK between May 2010 and April 2011. Methods Prospective case identification through the monthly mailing of UKOSS. Main outcome measures Median estimated blood loss, transfusion requirements. Results A cohort of 134 women were identified with placenta accreta, increta, or percreta: 50% (66/133) were suspected to have this condition antenatally. In women with a final diagnosis of placenta increta or percreta, antenatal diagnosis was associated with reduced levels of haemorrhage (median estimated blood loss 2750 versus 6100 ml, P = 0.008) and a reduced need for blood transfusion (59 versus 94%, P = 0.014), possibly because antenatally diagnosed women were more likely to have preventative therapies for haemorrhage (74 versus 52%, P = 0.007), and were less likely to have an attempt made to remove their placenta (59 versus 93%, P < 0.001). Making no attempt to remove any of the placenta, in an attempt to conserve the uterus or prior to hysterectomy, was associated with reduced levels of haemorrhage (median estimated blood loss 1750 versus 3700 ml, P = 0.001) and a reduced need for blood transfusion (57 versus 86%, P < 0.001). Conclusions Women with placenta accreta, increta, or percreta who have no attempt to remove any of their placenta, with the aim of conserving their uterus, or prior to hysterectomy, have reduced levels of haemorrhage and a reduced need for blood transfusion, supporting the recommendation of this practice.